P402 Is co-trimoxazole prophylaxis necessary for Inflammatory Bowel Disease patients receiving triple immunosuppression?. (27th May 2021) - Phillips, G; Moore-Gillan, C; Mohamed, Z; Mikin, P; Peake, S; Hicks, L
Abstract: Background: ECCO Guidelines (1) advocate Co-trimoxazole (TMP/SMX) prophylaxis against Pneumocystis jirovecii for patients with inflammatory bowel disease (IBD) on triple immunosuppression, although the evidence level is low and based on non-IBD patient data (2). We assessed adherence to this guidance and frequency of infection events among IBD patients at Imperial College Healthcare NHS Trust, London, UK. Methods: Eligible patients were defined as those on a combination of 2 immunosuppressants (with one of those being a biologic) between December 2017 to December 2020, who received a course of high dose steroids (≥20mg prednisolone). Patient demographics, IBD treatment, TMP/SMX prophylaxis and infections (including hospitalisation) developed within 30-days of starting high dose steroids were recorded retrospectively using the hospital electronic patient records. Results: In the cohort of 247 patients on concomitant biologic and immunosuppression dual therapy 176/247 (71%) were ≤ 49 years old and 136/247 (55%) were male. Over the three year observation period, 333 individual thiopurine-biologic combinations were prescribed; Of the biologics 157/333 (47%) were infliximab, 91/333 (27%) adalimumab, 50/333 (15%) vedolizumab, 27/333 (8%) ustekinumab and 8/333 tofacitinib (3%). All received azathioprine or 6MP concurrently. Steroids were prescribed on 75 occasions for 50 (20%) patients. Of 28/75 (37%) prescriptions where TMP/SMX was co-prescribed 4/28 (14%) developed infections with 1/28 (4%) requiring hospitalisation. There were no respiratory infections in this group. Of the 47/75 (63%) where TMP/SMX was not prescribed 7/47 (15%) developed infections (4/47 respiratory, 2/47 skin or bone, 2/47 [MZ1] gastrointestinal infections). One patient had 2 infections. The hospitalisation rate was 2/47 (4%). There were no confirmed cases of Pneumocystis jirovecii in either group. Conclusion: Existing evidence for TMP/SMX prophylaxis in this setting is limited and is reflected in the varied clinical practice observed. However, no difference in clinically significant infection rates among individuals with and without TMP/SMX prophylaxis was observed in our setting. Further data are required to validate the utility of antibiotic prophylaxis in severely immunosuppressed IBD cohorts to better guide its use. References: Rahier et al, Second European evidence-based consensus on the prevention, diagnosis and management of opportunistic infections in inflammatory bowel disease; JCC 2014 DiRienzo et al, Efficacy of trimethoprim-sulfamethoxazole for the prevention of bacterial infections in a randomized prophylaxis trial of patients with advanced HIV infection. AIDS Res Hum Retroviruses 2002